Sinonasal teratocarcinosarcoma: a case report - Priya, Thottukadavil S.; Andrews, Chakramakal Joseph; Kumar, S. Suresh; Divya, S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Sinonasal teratocarcinosarcoma (TCS) is a very rare malignant neoplasm of sinonasal tract with intermixed teratomatous, carcinomatous and sarcomatous elements. While the diagnosis is largely based on tissue analysis and immunohistochemistry, the mode of management demands further study. Surgical resection with or without chemotherapy and radiation therapy is currently the most accepted treatment regimen. Locally aggressive, while also associated with metastatic lesions, SNTCS is not easily resectable owing to its location and possible intracranial extension. Due to its aggressive nature over one-third of TCS tend to recur leading to treatment failure with a mean survival time of 1.9 years. Possible differentials include squamous cell carcinoma, olfactory neuroblastoma, adenocarcinoma, malignant mixed tumor of salivary gland type, undifferentiated carcinoma, malignant craniopharyngioma, mucoepidermoid carcinoma, transitional carcinoma of Schneiderian type and adenosquamous carcinoma. In this report, we present a case of TCS in a 55 years old male patient who presented to us with complaints of hyposmia, blurring of vision, diplopia and epiphora.